The curse of the werewolf : fantasy, horror and the beast within - Du Coudray, Chantal Bourgault (I.B. Tauris, 2006)
Half-man-half-myth, the werewolf has over the years infiltrated popular culture in many strange and varied shapes, from Gothic horror to the 'body horror' films of the 1980s and today's graphic novels. Yet despite enormous critical interest in myths and in monsters, from vampires to cyborgs, the figure of the werewolf has been strangely overlooked. Embodying our primal fears - of anguished masculinity, of 'the beast within' - the werewolf, argues Bourgault du Coudray, has revealed in its various lupine guises radically shifting attitudes to the human psyche. Tracing the werewolf's 'use' by ant.